Acidity-responsive gene delivery for "superfast" nuclear translocation and transfection with high efficiency. (March 2016) - Zhu, Jing-Yi; Zeng, Xuan; Qin, Si-Yong; Wan, Shuang-Shuang; Jia, Hui-Zhen; Zhuo, Ren-Xi; Feng, Jun; Zhang, Xian-Zheng
Abstract: In principle, not only efficient but rapid transfection is required since it can maximize the bioavailability of vector-carried gene prior to the cellular excretion. However, the "rapid" goal has been paid few attentions so far in the research field of vector-aided transfection. As a pioneering attempt, the present study designed a lysosome-targeting acidity-responsive nanoassembly as gene vectors, which proved the amazing potency to mediate the "Superfast" transnuclear gene transport and gene transfection with high efficiency in vitro and in vivo . The nanoassembly was constructed on the pH-reversible covalent boronic acid-diol coupling between 1, 3-diol-rich oligoethylenimine (OEI-EHDO) and phenylboronic acid modified cholesterol (Chol-PBA). The rapid and efficient nuclei-tropic delivery and transfection was demonstrated to highly rely on the lysosome-acidity induced assembly destruction followed by the easy liberation of gene payloads inside cells. The nanoassembly-mediated transfection at 8 h can afford the outcome even comparable to that achieved at 48 h by the golden standard of PEI25k, and the transfection efficiency can still remain at a high level during 48 h. In contrast, time-dependent efficiency enhancement was identified for the transfections using PEI25k and OEI-EHDO as delivery vectors. Moreover, owing to the hydroxyl-rich surface, this delivery nanosystem presented strong tolerance to the serum-induced transfection inhibition that frequently occurred for the polycationic gene vectors such as PEI25k. The in vitro and in vivo results manifested the low toxicity of this bio-decomposable nanoassembly.